Macroporous scaffolds based on biomass polymers and their applications in wound healing - Daqian Gao; William D. Shipman; Yaping Sun; Joshua Zev Glahn; Leleda Beraki; Henry C. Hsia (Journal of Bioresources and Bioproducts)
The rapid advancement of biomedical polymers has raised significant concerns about the disposal of medical polymer waste. Sustainable biomass materials derived from renewable sources in nature have emerged as promising alternatives to petroleum-based polymers for medical applications and tissue engineering due to their abundance, biodegradability, and environmental friendliness. In tissue engineering, interconnected macropores within biomaterials are crucial as they provide space and interfaces for cells, enhancing permeability for nutrient and waste transport. In this review, we summarize recent developments in the use of biomass materials to engineer macroporous tissue engineering scaffolds. We highlight key techniques, such as microparticles assembly, leaching template, and bioprinting that can create macropores within scaffolds composed of biomass materials and their composites. In addition, we investigate the applications of the macroporous scaffolds in wound healing, with a focus on cell behaviors within macroporous constructs and their role in treating chronic wounds. We envision that the combination of the bicontinuous macropores and biomass-based materials can create an ideal cellular environment and provide a powerful platform for wound healing and tissue regeneration.